ASSESSMENT OF THE CYBER SPACE PROTECTION LEVEL IN PUBLIC GOVERNANCE: NATIONAL AND ORGANIZATIONAL DIMENSION - Kotukh , Ye. (Theory and Practice of Public Administration, 2021)
The article examines the features and main directions of cybersecurity in public administration. It is established that the state in general and public administration authorities, in particular, are not ready today to adequately respond to the main cyber threats related to information theft, financial fraud and hacker attacks. The success of the implemented cybersecurity strategies depends on a clear justification of the feasibility of measures based on the identification of key issues in this area. In such conditions, a permanent assessment of the cyberspace protection level in public administration is necessary. In this regard, the aim of the article was to assess the current level of cyberspace protection in the public sector in the national and organizational dimensions, as well as to justify ways to increase cyber protection in the field of public administration. In order to clarify the information about cybersecurity state in Ukraine in modern conditions, an all-Ukrainian expert sociological survey was conducted. The current cybersecurity state is analyzed, as well as ways to increase its level in the field of public administration at the national and organizational levels. The identified problems are due to the imperfection of public policy in this area, as well as the high cost of relevant equipment and programs. It is determined that common to all persons working in public administration is the need to master the technologies of electronic document management and online communications, which are related to the specifics of their work. The priority ways to increase the level of cybersecurity in the public sector in modern conditions should be to increase budget funding, strategic investment in cyber analytics and cloud technologies, the creation of special units for cybersecurity, installation of modern software and its constant updating, regular training of employees involved in matters of organizational and personal information protection.